Transient and Quasi‐Equilibrium Climate States at 1.5°C and 2°C Global Warming. Issue 11 (27th October 2021) - King, Andrew D.; Borowiak, Alexander R.; Brown, Josephine R.; Frame, David J.; Harrington, Luke J.; Min, Seung‐Ki; Pendergrass, Angeline; Rugenstein, Maria; Sniderman, J. M. Kale; Stone, Dáithí A.
Abstract: Recent climate change is characterized by rapid global warming, but the goal of the Paris Agreement is to achieve a stable climate where global temperatures remain well below 2°C above pre‐industrial levels. Inferences about conditions at or below 2°C are usually made based on transient climate projections. To better understand climate change impacts on natural and human systems under the Paris Agreement, we must understand how a stable climate may differ from transient conditions at the same warming level. Here we examine differences between transient and quasi‐equilibrium climates using a statistical framework applied to greenhouse gas‐only model simulations. This allows us to infer climate change patterns at 1.5°C and 2°C global warming in both transient and quasi‐equilibrium climate states. We find substantial local differences between seasonal‐average temperatures dependent on the rate of global warming, with mid‐latitude land regions in boreal summer considerably warmer in a transient climate than a quasi‐equilibrium state at both 1.5°C and 2°C global warming. In a rapidly warming world, such locations may experience a temporary emergence of a local climate change signal that weakens if the global climate stabilizes and the Paris Agreement goals are met. Our research demonstrates that the rate of global warming must be considered in regional projections. Plain Language Summary: The world has warmed quickly since around 1970, prompting efforts to mitigate climate change and to stabilize global temperatures between 1.5°C and 2°C above pre‐industrial levels. We explore the differences between a rapidly warming climate and one with little change in global temperature over time. We find that a fast‐warming climate is characterized by warmer temperatures over Northern Hemisphere mid‐latitude land regions than a stable climate at the same level of global warming. The opposite is true in the Southern Ocean where slower warming occurs because of the lag in warming of the deep ocean, so as the global climate stabilizes that region continues to warm. As the world continues to warm, some land locations, such as the interior of North America and Eurasia, may experience a temporary emergence of a climate change signal that weakens if the climate stabilizes and the Paris Agreement goals are met. The difference between fast‐warming and stable climates can be very large locally, so they must be considered in planning for adapting to future climate change. Key Points: Warming patterns at Paris Agreement limits differ substantially between transient and quasi‐equilibrium climates Summer climate changes over northern land are clearer in a transient climate than a stabilized climate at the same global warming level Projections of regional climate designed for the Paris Agreement limits are only useful if the rate of global warming is explicit